2019
DOI: 10.1017/ice.2019.112
|View full text |Cite
|
Sign up to set email alerts
|

Creating reasonable antibiograms for antibiotic stewardship programs in nursing homes: Analysis of 260 facilities in a large geographic region, 2016–2017

Abstract: Objective:To determine the best nursing home facility characteristics for aggregating antibiotic susceptibility testing results across nursing homes to produce a useful annual antibiogram that nursing homes can use in their antimicrobial stewardship programs.Design:Derivation cohort study.Setting:Center for Medicare and Medicaid Services (CMS) certified skilled nursing facilities in Georgia (N = 231).Participants:All residents of eligible facilities submitting urine culture specimens for microbiologic testing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…These results are similar to common pathogens reported from either UTI or urine cultures from nursing home residents in other studies. 4,[14][15][16][17][18] Within nursing homes, levels of antibiotic resistance, including MDR, were generally higher among the CA-SUTI events than UTIs not associated with catheters, most notably for vancomycin resistance in E. faecium and extended-spectrum cephalosporin and carbapenem resistance in Klebsiella spp. These differences observed among nursing-home UTI event types may be explained by the role that biofilm formation on indwelling devices plays in the selection and emergence of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to common pathogens reported from either UTI or urine cultures from nursing home residents in other studies. 4,[14][15][16][17][18] Within nursing homes, levels of antibiotic resistance, including MDR, were generally higher among the CA-SUTI events than UTIs not associated with catheters, most notably for vancomycin resistance in E. faecium and extended-spectrum cephalosporin and carbapenem resistance in Klebsiella spp. These differences observed among nursing-home UTI event types may be explained by the role that biofilm formation on indwelling devices plays in the selection and emergence of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, investigators in Georgia evaluated 231 nursing homes and found that only 10% of nursing homes had sufficient test results from common urinary pathogens in a given year to fulfill the CLSI guidance. 25 Sputum and skin cultures were even less frequent. The risks inherent when using unreliable estimates (ie, fewer than 30 isolates) includes inappropriately using potentially more toxic and/or ineffective agents during empiric therapy.…”
Section: Reliabilitymentioning
confidence: 99%
“…Based on the Georgia nursing home study, combining 3 years of data for urinary pathogens would allow enough isolates for the majority of nursing homes. 25 Although this may obscure some shifts in resistance patterns, it is unlikely to be of clinical significance in such a short time period. This is probably the most inherently reliable method for the laboratory to perform.…”
Section: Reliabilitymentioning
confidence: 99%
See 2 more Smart Citations